ALOKASI WAKTU KERJA WANITA DAN SUMBANGANNYA TERHADAP PENDAPATAN RUMAH TANGGA PETANI DI KECAMATAN BATURRADEN, KABUPATEN BANYUMAS ALLOCATION OF WOMAN WORK TIME AND ITS CONTRIBUTION ON FARMERâS HOUSEHOLD INCOME AT BATURRADEN DISTRICT, BANYUMAS REGENCY - , Sundari; , Sundari; Sriningsih, Endang; K.E., Adwi Herry (Pembangunan Pedesaan, 2005)
This research aimed at calculating on-farm and off-farm woman work time allocation and its contribution to farmerâs household income, understanding factors influencing the allocation, and analyzing between the allocation and family decision maker. Survey was used as research method and purpose was used for area samples at Baturraden District. Sample was obtained by cluster random sampling method. Data was analyzed by descriptive, OLS, and Harvard Analysis. Research result showed that the allocation was 271 hours per year or 1.732 hours per day. The contribution of woman labor to farmer on farmerâs household income was Rp 484,863.3 per year (4.33%). The off-farming contribution was Rp 2,177,368.8 per year (19.44%). Factors influencing negative significantly on the allocation was household and off-farm woman work allocation. Meanwhile, on-farm man work factor influenced positive significantly. Interaction between woman work time allocation and family or household decision maker had closely proportional relationship especially at social and household activity decision maker. On the other hand, man and woman position was equal for making decision. At productive field, however, control and decision was still dominated by man. Key words: Farmerâs household income, Woman work time